ANALISIS KEAMANAN JARINGAN WIFI MAHASISWA UBD DARI SERANGAN PACKET SNIFFING - ARIYADI, TAMSIR; Irwansyah, Irwansyah; Huda Mubarok, M. Syaiful (JURNAL ILMIAH INFORMATIKA, 2024)
The wifi network of Bina Darma University is open to potential attacks by hackers, as they are unavoidably carried out. Network security is the act of recognizing and blocking unwanted users, or intruders, from computer networks. It serves as a safeguard for a network system against unauthorized and careless network users. In this study, the "Experiment Method" is employed. One approach that seeks to both test and explain an event is the experiment technique. Using the tools ettercap and wireshark, tests on network security were run and the findings analyzed for this study. The study's findings show that the network security encryption utilized at Bina and the security mechanism on the ubd student wifi network are both in good working order.